Az első világháború muzealizálása egy vidéki múzeum példáján - Mód László; A Nagy Háború hatása a mindennapok kultúrájának változására (2015) (Szeged) (2018)
The author deals with the muzealization process of the WWI whichwas arranged in the museum of Szentes. The director of the institution was very active who started to collect the items from the beginning of the Great War. Between the two worlds war period a rich military collection was developed which contains different objects and documents. It looks like that the heartland was interested in these pieces that’s why some of them were exhibited. These objects brought closer the war, because local people had a possibility to get acquainted withthe military utensils.
Keywords: Bölcsészettudományok; Történettudomány és régészet